Properties of pig synovial collagenase. - Tyler, J A (1980)
1. Properties of a purified chemically activated form of pig synovial collagenase were examined and compared with a spontaneously active form of the enzyme. 2. The active enzyme has a specific activity of 53 000 units (microgram/min)/mg, a mol.wt. of 44 000 (by sodium dodecyl sulphate/polyarcylamide-gel electrophoresis in 2-mercaptoethanol) and pI 5.2 (by isoelectric focusing in polyacrylamide gels). 3. The activity has the characteristics of a metalloproteinase that degrades types I and III soluble or insoluble collagens in preference to type II, at an optimum pH of 6.5-8.5. 4. There is no detectable difference in these properties between the chemically activated and spontaneously active form of collagenase.